Criminal Crews, Codes, and Contexts: Differences and Similarities across the Code of the Street, Convict Code, Street Gangs, and Prison Gangs. Issue 10 (3rd October 2017) - Mitchell, Meghan M.; Fahmy, Chantal; Pyrooz, David C.; Decker, Scott H.
ABSTRACT: We use 16 characterizations of crews, codes, and contexts to determine if offender subcultures (code of the street, convict code, street and prison gangs) converge, complement, or are independent of one another. We find extensive overlap across offender subcultures with "belief" subcultures in street and prison settings mirroring the "group" subcultures in those respective settings. Findings generate a call for comparative research on the convergences and divergences across subcultures on the street and in prisons with a specific emphasis on the impact that importation, deprivation, and exportation have on policy and programming importation for both the street and prison settings.